TEMA NASIONALISME DALAM PEMBELAJARAN SASTRA: UPAYA MENUMBUHKAN SEMANGAT KEBANGSAAN* - Lustantini Septiningsih (KAJIAN SASTRA, 2010)
Nowdays, we have a lot of corruption, proverty, injustice, and bribery in our county. These symptoms show the attitude of our society which tend to be selfish so that they less pay attention to their surroundings, whereas our country known as prosperous country and the people are friendly and polite. Youth as a part of society who will be the next leader of this country, their nationalism should be awaken in order that their enthusiasm of nationally is strong. If it is not anticipated, that condition will make their enthusiasm of nationaly annihilated. Meanwhile, it will be needed a leader which have perception of nationally leadership to build perception of nationality which empty into national integration. It means that how important it is to strenghten enthusiasm of nationality to youth because they are the hope of nation and state to continue estafette of nation leadership. One of the ways to plant enthusiasm of nationality is through literary learning with nationalism theme. Literary teaching at school can be mean to make enthusiasm of nationality better by introducing and conveying masterpiece in Indonesia literary words to students. So, this paper will also see literary words which choosen in literature handbooks whether nationalism topic have an attention.